Efektivitas Sistem Penilaian Kinerja Guru dan Pengelolaan Dana Bantuan Operasional Sekolah (Bos) dalam Meningkatkan Sarana dan Prasarana Pendidikan: Studi Kasus di SDN 47 Cakranegara Mataram dari Perspektif Manajemen Sumber Daya Manusia - Jumiati; Aprianingrum, Rahayu; Berliani, Ketty; Dwi Harna, Safira; Hidayat, Rahmad (Samsara Institute Publisher, 2025)
Education is a crucial aspect in regional and state development, influencing the quality of human resources and the progress of the nation. This research evaluates the effectiveness of the teacher performance assessment system and management of School Operational Assistance Funds (BOS) in improving facilities and infrastructure at SDN 47 Cakranegara Mataram. Qualitative research methods with a case study design were used, including in-depth interviews, observation, and document analysis. The research results show that the teacher performance appraisal system is effective with an average percentage of 79.8%, has a positive impact on teacher motivation and engagement. Management of BOS funds is also effective with an average percentage of 82.6%, especially in terms of the impact on educational facilities. There is a positive relationship between these two factors, where good performance appraisals motivate teachers to contribute to facilities needs, while optimal management of BOS funds improves school facilities. It is recommended that the assessment system be improved to include more feedback, and that the management of BOS funds be clarified to better suit school needs. These findings are expected to provide insight for education managers and policy makers in improving the quality of education in Indonesia.